PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE MELALUI EMPLOYEE JOB SATISFACTION DAN INNOVATION PADA PERUSAHAAN RETAIL DI SURABAYA - Ocsakawati, Serley (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to financial performance, leadership style to employeeâs job satisfaction, leadership style to innovation, employeeâs job satisfaction to innovation , employeeâs job satisfaction to financial performace, and innovation to financial performace on retail firms in Surabaya. This study also aimed to examine the indirect and significant affect of leadership style to financial performance through employeeâs job satisfaction and innovation in retail firms in Surabaya.Â Â Â Â Â  This study used quantitative approach, whereas the data obtained through the distribution of questionnaire to retail firms in Surabaya. The data obtained processed by using smartPLS software. The result showed that there was positive and significant relationship of leadership style to employeeâs job satisfaction, leadership style to innovation, leadership style to financial performance, employeeâs job satisfaction to innovation, employeeâs job satisfaction to financial performance, and negative and significant relationship affect of innovation to financial performance on retail firms in Surabaya. Employeeâs job satisfaction and innovation became as the intervening variable to leadership style and financial performance because the direct relationship between leadership style and financial performance gave larger affect than through innovation and employee job satisfaction.